Fourier Transform Infrared (FTIR) Spectroscopy of Humic Acid from Chicken Manure Compost with Different Biodecomposers: Spectroskopi Fourier Transform Infrared (FTIR) Asam Humat dari Kompos Kotoran Ayam dengan Biodekomposer Berbeda - Noorhidayah, Ratri; Musthafa , Muhammad Bachtiar; Sisno (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Humic acid is the final compound resulting from decomposition and humification so that it is more resistant. The role of humic acid includes: reinforcing agents to increase the efficiency of electrokinetic remediation from arsenic contamination, limiting the toxicity of Cd and Pb to earthworms in the soil, cementing agents in the soil matrix to suppress environmental degradation of mineral mining. The research was conducted to obtain humic acid extract from compost of agricultural and livestock waste. Humic acid is extracted from compost using strong acids and strong bases. Compost from chicken manure is expected to be a solution for livestock waste that has the potential to pollute the environment. The composting of chicken manure is combined with agricultural waste and weeds such as straw, corncob, banana weevil, durian skin and water hyacinth. Decomposition was carried out with the help of EM4 biodecomposer, Compost Yeast and Earthworms. The functional groups that characterize humic acid from chicken manure compost with a variety of additives and biodecomposers are the absorption peak 3450 - 3300 cm-1, 2980-2920 cm-1, 1660-1630 cm-1 and 1170-950 cm-1. The low degree of humification in all treatments is a characteristic of effective compost with the barrel. EM4 is most effective at increasing the rate of decomposition of organic matter in the treatment